PENGEMBANGAN LKPD BERBASIS PROBLEM SOLVING BERBANTUAN SOFTWARE TRACKER UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH DI SMA - Emi Risa; Lukman Hakim; Dwi Ratnaningdyah; Rita Sulistyowati (Universitas Negeri Gorontalo, 2021)
Development research has been carried out to produce student worksheets (LKPD) based on problem-solving assisted by tracker software that is valid, practical, and has the potential effect of improving problem-solving skills. This research is development research (R and D) that uses the Rowntree model which consists of the planning stage, the development stage, and the evaluation stage, which includes self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field test. The subjects in this study were students of class X SMA in Palembang. Based on the expert review stage, the validity of the LKPD based on problem-solving assisted by tracker software in terms of the feasibility of the material, language, and learning design obtained an average value of 90% with the very valid category. The one-to-one stage obtained an average value of 87% in the very practical category. The small group stage obtained an average score of 86% in the very practical category. In the field test stage, 91% of students completed the physics questions and the post-test results showed an increase of 50 when compared to the pre-test results.